Videothoracoscopic treatment of oesophageal leiomyoma. Issue 3 (1st March 1998) - Roviaro, G C; Maciocco, M; Varoli, F; Rebuffat, C; Vergani, C; Scarduelli, A
Abstract : BACKGROUND: Oesophageal leiomyomas are usually so easily removed that thoracotomy seems out of proportion and thoracoscopic removal is therefore highly desirable. METHODS: Out of a total of 1003 thoracoscopic operations undertaken between July 1991 and December 1996, seven patients underwent thoracoscopic removal of oesophageal leiomyoma. All of them had been preoperatively studied by oesophagogastroscopy and computed tomographic scanning of the chest which had confirmed the presence of a lesion with benign features. The surgical technique required intubation with a double lumen tube. Operative access was gained through the right chest via three ports and a small utility thoracotomy in the inframammary sulcus. The mean operating time was 120 minutes. RESULTS: Conversion to open thoracotomy was necessary in one case with a very large horseshoe-shaped leiomyoma which was firmly adherent. The mean postoperative hospital stay was seven days. No intraoperative deaths or postoperative complications occurred. CONCLUSIONS: The simplicity and safety of the thoracoscopic approach, combined with reduced surgical trauma and postoperative pain and functional and cosmetic advantages, make this technique the approach of choice for the removal of oesophageal leiomyomas.